Electrochemically Activated Water Police Crops With Microelement Solution Processing Before Planting - Yusupova Maxpuza Numanovna (Zien Journals, 2024)
The article presents the results of preliminary studies conducted on the treatment of pumpkin seeds with a solution of microelements of electrochemically activated water before sowing and studying the effect on plant growth and development.
Keywords: Electrochemically activated water; microelements; pumpkin seeds